2017
DOI: 10.1590/1678-4162-9395
|View full text |Cite
|
Sign up to set email alerts
|

Histological evaluation and E-cadherin and β-catenin expression in kidney of dogs submitted to renal ischemia and reperfusion after chlorpromazine administration

Abstract: Renal ischemia can be associated with some urological procedures, such as renovascular surgery or kidney transplantation, that are often followed by acute renal failure. The aim of this study was to verify the E-cadherin and β-catenin localization in canine kidney in different times of renal ischemia and reperfusion after chlorpromazine application. Twelve dogs were randomly distributed equally into two groups. GroupA with ischemia and reperfusion without chlorpromazine and groupB with ischemia and reperfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…They revealed that E-cadherin is differentially expression in medulla and cortex. E-cadherin expression was increased in after IR injury 18 . In our study, in the control group, E-cadherin expression was positive in basement membrane, but generally negative.…”
Section: Discussionmentioning
confidence: 88%
“…They revealed that E-cadherin is differentially expression in medulla and cortex. E-cadherin expression was increased in after IR injury 18 . In our study, in the control group, E-cadherin expression was positive in basement membrane, but generally negative.…”
Section: Discussionmentioning
confidence: 88%